Optimizing Penal Mediation through Restorative Justice: A Progressive Solution in Criminal Law Reform - Arpangi, Arpangi; Ramadani , Maydika; Cindy Yosiana (Jurnal Justice Dialectical, 2024)
In Indonesia, prison mediation by restorative justice has evolved as a progressive approach to criminal justice reform to create a more compassionate, efficient, and rehabilitative justice system. Despite its promise, its implementation confronts problems such as a lack of knowledge among law enforcement personnel and the general public and regulatory inadequacies. This paper intends to evaluate the application of penal mediation as an alternative to conventional criminal justice processes, analyzing its role in attaining restorative justice and its efficacy in resolving minor offenses and child-related issues. This study examines prison mediation through restorative justice in the Indonesian criminal law system using a normative juridical technique combined with a qualitative descriptive-analytical methodology. Data were gathered from literature reviews and associated legal documents, and the analysis was done utilizing a deductive-inductive technique to combine theory and practice in criminal law reform. According to the findings, introducing prison mediation via restorative justice can substantially contribute to revamping Indonesia's criminal justice system, notably by decreasing the load on courts and offering a more rehabilitative approach for offenders. The study emphasizes the significance of matching legislative frameworks, such as the Penal and Draft Criminal Procedure Code, with restorative justice ideas for easier integration. Furthermore, research demonstrates that the practical application of restorative justice has ongoing hurdles, notably in terms of legal understanding and institutional preparation. The report proposes enhancing training for legal practitioners and extending public awareness campaigns to increase the efficacy of restorative justice in Indonesia.